Ultrasound Shear Wave Elastography, Shear Wave Dispersion and Attenuation Imaging of Pediatric Liver Disease with Histological Correlation - Ivan Cetinic; Charlotte de Lange; Yvonne Simrén; Nils Ekvall; Maja Östling; Liselotte Stén; Håkan Boström; Kerstin Lagerstrand; Hanna Hebelka (MDPI AG, 2022)
Aim: To evaluate the feasibility of multiple ultrasound markers for the non-invasive characterization of fibrosis, inflammation and steatosis in the liver in pediatric patients. Materials and methods: The quantitative ultrasound measures shear wave elastography (SWE), shear wave dispersion (SWD) and attenuation imaging (ATI) were compared and correlated with percutaneous liver biopsies and corresponding measures in a control cohort. Results: The median age of the 32 patients was 12.1 years (range 0.1-17.9), and that of the 15 controls was 11.8 years (range: 2.6-16.6). Results: There was a significant difference in SWE values between histologic grades of fibrosis (p = 0.003), with a positive correlation according to the grade (r = 0.7; p < 0.0001). Overall, a difference in SWD values between grades of inflammation was found (p = 0.009) but with a lack of correlation (r = 0.1; p = 0.67). Comparing inflammation grades 0-1 (median:13.6 m/s kHz [min; max; 8.4; 17.5]) versus grades 2-3 (16.3 m/s kHz [14.6; 24.2]) showed significant differences between the groups (p = 0.003). In the 30 individuals with a steatosis score of 0, ATI was measured in 23 cases with a median value of 0.56 dB/cm/MHz. Conclusion: Comprehensive ultrasound analysis was feasible to apply in children and has the potential to reflect the various components of liver affection non-invasively. Larger studies are necessary to conclude to what extent these image-based markers can classify the grade of fibrosis, inflammation and steatosis.